Effects of Isalo scorpion cytotoxic peptide on growth, immune performance, and intestinal flora of yellow-feathered broilers - Wang, Zhengli; Zhu, Jianjun; Ma, Yan; Liu, Tingting; Chen, Shuaihu; Gao, Mingyang; Wang, Sijia; Wang, Jungang; Shen, Hong (Frontiers in Veterinary Science, 2024)
IntroductionThis study aimed to investigate the effects of Isalo scorpion cytotoxic peptide (IsCT) on the growth performance, immune function, and gut microbiota of yellow-feathered broilers.MethodsThe experiment involved supplementing a corn-soybean meal-based diet with various dietary levels of IsCT. The experiment adopted a completely randomized design. A total of 240 one-day-old yellow-feathered broilers were randomly divided into six groups: a control group (CON), a chlortetracycline group (CTC), and four groups receiving a basal diet with 50, 100, 150, or 200 mg/ kg IsCT (IsCT50, IsCT100, IsCT150, and IsCT200). The trial period lasted 60 days.ResultsThe results showed that the average final body weight and average daily weight gain of the IsCT150 and IsCT200 groups were significantly higher than those of the CON group (p < 0.05). Compared to the CTC group, the average daily feed intake in group III was significantly lower (p < 0.05). The feed conversion ratios of the IsCT150 and IsCT200 groups were significantly lower than those of the IsCT50 and CON groups (p < 0.05). Albumin levels in the CTC and IsCT150 groups were significantly higher than those in the CON, IsCT100, and IsCT50 groups. Alanine transaminase levels in the IsCT150 group were significantly lower than those in the IsCT50, IsCT200, CON, and CTC groups (p < 0.05), but there was no significant difference compared with the IsCT100 group (p < 0.05). IgA levels in the IsCT150, IsCT200, and CTC groups were significantly higher than those in the IsCT50 group (p < 0.05). IgG levels in the CTC, IsCT100, IsCT150, and IsCT200 groups were significantly higher than those in the IsCT50 and CON groups (p < 0.05). 16S rRNA sequencing indicated significant differences in the caecal microbiota between the IsCT and CON groups (p < 0.05). The abundance of Bacteroidetes increased, whereas that of Firmicutes decreased in the IsCT groups; however, the difference was not significant (p < 0.05). The relative abundances of Actinobacteriota and Patescibacteria were significantly different in the IsCT100 group (p < 0.05).DiscussionIn conclusion, supplementing the basal diet with IsCT improved growth performance, immune function, and gut microbiota of yellow-feathered broilers at an optimal supplementation level of 150 mg/kg.